How do managers and physicians reconcile between financial and clinical considerations in hospitals?. (30th September 2020) - Waitzberg, R; Quentin, W; Gottlieb, N; Busse, R; Greenberg, D
Abstract: Background: Hospital managers and physicians may face dilemmas due to their role as dual agents, committed both to their hospitals and their patients. We aim to pinpoint situations where economic and clinical considerations are aligned or conflicting; and to explore how managers and physicians reconcile different considerations in their decision-making in Germany and Israel. Methods: Qualitative, thematic analysis based on 47 in-depth interviews with managers, ward directors and physicians in five hospitals in Germany and five in Israel. Results: Economic and clinical considerations are aligned when gaps between hospital payments and costs are small, and economic incentives do not distort clinical considerations or when good medicine avoids complications while saving costs. Dilemmas arise when procedures are underpriced, resulting in financial losses to the hospital, and represent barriers for adoption of new, costly, medical equipment. In many instances, managers and ward directors choose one of the principals (hospital or patient), yet sometimes they develop reconciliation strategies that include: (1) improving coding of activities and diagnoses to assure higher payments; (2) reducing costs per case by choosing cheaper supplies with the same quality, bulk purchasing or reducing unnecessary lengths-of-stay; (3) providing clear treatment guidelines that support decision-making. Hospitals in Germany increase efficiency through specialization, and try to find alternative, less costly, care settings such as rehabilitation facilities. In Israel, hospitals balance the amount of unprofitable cases with many other profitable cases. Conclusions: While sometimes one principal prevails, agents reconcile economic and clinical considerations. In Germany, a high-expenditure hospital market, there is some flexibility to change the character of hospitals activity, while in Israel, a middle-expenditure market, agents balance activities within the existing framework. Key messages: Dilemmas exist regardless of the amount of hospitals' funds. In Germany there is flexibility to change hospitals' activity, while in Israel agents balance activities within the existing framework.